PEOPLE’S AGES AND THE EFFECTIVENESS OF USING ACTIVITIES IN THE BUILT ENVIRONMENT OF COMMERCIAL STREETS - Khalaf, Omar Abdulwahhab; Ja`afar, Nor Haslina; Harun, Nor Zalina; Bayaty, No’man; Mohammed, Noraziah (PLANNING MALAYSIA, 2022)
Streets are the most public of all city spaces and are utilised by all users. Therefore, activities are vital in persuading people to use the streets and in presenting the image of the city. The relation between people’s ages and the used activities of the commercial streets has declined due to the poor physical environments in the local context. Streets have become progressively unpleasant, unsuitable in terms of functions, and have also become a disagreeable environment. This represents the problem statement of this research. The objective of this paper is to examine the relationship between activities on commercial streets and the different age groups of the users. This study focuses on the local context of Mawlawi Street, which is one of the major shopping streets in Sulaymaniyah city centre, Iraq. This paper used a quantitative methodology via a survey of users (n = 330). The data were analysed using frequency, mean value, percentage, and chi-square statistics. The results show that cultural activities were the most important for its users, while social activities were the least important, with businesses in the middle. The majority of the users were in the young-adults age category. The research gives a good overview of the types of activities which encourage high street usage, and which activities need to be improved or added.